KETERAMPILAN BERBICARA SISWA DENGAN SELF-ESTEEM RENDAH DI SMP GLOBAL ISLAMIC BOARDING SCHOOL (GIBS) BARITO KUALA - Istiqamah Dyta Setiawati Hariyono (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2020)
Abstract Skills Talking Students With Low Self-Esteem At The Junior High Schools Global Islamic Boarding School (GIBS) Barito Kuala. Speaking is the main means of fostering mutual understanding, mutual communication, using language as its medium. Speaking activities in language classes have aspects of two-way communication, namely between the speaker and listeners reciprocally (Ngalimun & Alfulaila: 2014: 55). The purpose of this study is to provide an overview of the speaking skills possessed by GIBS Middle School students who have low self-esteem. The stages of this research method use descriptive qualitative research methods. The data in this study were oral and written data in the form of observations, oral interviews, and written questionnaires. The data source in this study is GIBS Middle School students who have low self-esteem. In SMP GIBS, out of 107 students there were 5 people (4.67%) students classified as having high self-esteem, 95 people (88.79%) students were classified as having moderate self-esteem, and 7 people (4.67%) students are classified as having low self-esteem. From this data, further action is taken on students who have low self-esteem in the form of interviews, storytelling through arranged images, and group discussion forums (FGD). From the follow-up actions, it was found that there are several aspects that can describe a person's speaking skills, namely aspects of the quantity of sentence production, sentence quality (the appropriateness of the answers to the questions during the interview / question and answer), structure, and diction. Key words: speaking skills, self-esteem Abstrak Keterampilan Berbicara Siswa dengan Self-Esteem Rendah di SMP Global Islamic Boarding School (GIBS) Barito Kuala. Berbicara merupakan sarana utama untuk membina saling pengertian, komunikasi timbal balik, dengan menggunakan bahasa sebagai medianya. Kegiatan berbicara di dalam kelas bahasa mempunyai aspek komunikasi dua arah, yakni antara pembicara dengan pendengar secara timbal balik (Ngalimun & Alfulaila: 2014:55). Tujuan penelitian ini adalah untuk memberikan gambaran mengenai keterampilan berbicara yang dimiliki oleh siswa SMP GIBS yang memiliki self-esteem rendah. Tahapan metode penelitian ini menggunakan metode penelitian kualitatif deskriptif. Data dalam penelitian ini adalah data lisan dan tulisan berupa pengamatan, wawancara secara lisan, dan angket tertulis. Sumber data dalam penelitian ini adalah siswa SMP GIBS yang mempunyai self-esteem rendah. Di SMP GIBS, dari 107 orang siswa terdapat 5 orang (4,67%) siswa tergolong mempunyai self-esteem tinggi, 95 orang (88,79%) siswa tergolong mempunyai self-esteem sedang, dan 7 orang (4,67%) siswa tergolong mempunyai self-esteem rendah. Dari data tersebut, dilakukan tindakan lanjutan terhadap siswa yang mempunyai self-esteem rendah berupa wawancara, bercerita melalui gambar yang dirangkai, dan forum group discussion (FGD). Dari tindakan lanjutan tersebut didapatkan hasil bahwa terdapat beberapa aspek yang dapat mendeskripsikan keterampilan berbicara seseorang, yaitu aspek kuantitas produksi kalimat, kualitas kalimat (kesesuaian jawaban dengan pertanyaan pada saat wawancara/tanya jawab), struktur, dan diksi. Kata-kata kunci: keterampilan berbicara, self-esteem